2008
DOI: 10.1016/j.ijid.2008.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology and risk factors of bloodstream infections caused by extended-spectrum β-lactamase-producing Klebsiella pneumoniae

Abstract: The prevalence of ESBL-Kp was found to be lower than that previously reported in Latin America. ESBL-Kp bacteremia was not associated with a worse clinical outcome. We were able to identify a plasmid-mediated horizontal dissemination over the 10-year period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0
5

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 23 publications
4
26
0
5
Order By: Relevance
“…Mortality rates following K. pneumoniae bacteremia ranged from 27.4 to 37% (33,(80)(81)(82)(83). The higher risk of mortality due to K. pneumoniae bacteremia is associated with a number of patient factors, including patients being admitted to the ICU, being more than 65 years old, having an underlying malignancy, presenting with pneumonia, requiring mechanical ventilation or urinary catheters, or being alcoholics (33,(80)(81)(82)(83)(84). Of grave concern to the medical community is the increase in antibiotic resistance that makes treatment of lung and bladder K. pneumoniae infections more difficult and extends the length of time that patients carry K. pneumoniae at these sites, allowing more opportunities for K. pneumoniae to spread to the bloodstream and brain.…”
Section: Infections Caused By K Pneumoniaementioning
confidence: 99%
“…Mortality rates following K. pneumoniae bacteremia ranged from 27.4 to 37% (33,(80)(81)(82)(83). The higher risk of mortality due to K. pneumoniae bacteremia is associated with a number of patient factors, including patients being admitted to the ICU, being more than 65 years old, having an underlying malignancy, presenting with pneumonia, requiring mechanical ventilation or urinary catheters, or being alcoholics (33,(80)(81)(82)(83)(84). Of grave concern to the medical community is the increase in antibiotic resistance that makes treatment of lung and bladder K. pneumoniae infections more difficult and extends the length of time that patients carry K. pneumoniae at these sites, allowing more opportunities for K. pneumoniae to spread to the bloodstream and brain.…”
Section: Infections Caused By K Pneumoniaementioning
confidence: 99%
“…17 For this reason, it is important to clarify these issues for the design of strategies aimed at reducing resistances. Other variables associated with the identification of ESBL-producing strains in patients with bloodstream infection reported in the literature are the patient's age, 15 severe underlying diseases, 13 renal transplantation, 13 previous admission to the ICU, 18 duration of hospitalization before bacteremia, 19 prior exposure to urinary catheters, 10,14,16 invasive procedure within the previous 72 hours, 16 and the nosocomial origin of bacteremia. 10 In a systematic review of studies evaluating the association between inappropriate antibiotic therapy and mortality among bacteremic patients, measurement of severity of illness without specified the time at which it was measured was considered a source of methodological heterogeneity that may explain conflicting findings.…”
mentioning
confidence: 99%
“…23 For example, a retrospective case-control study that included all cases of K. pneumoniae bacteremia from a single center in Mexico (1993Mexico ( -2002 reported that an ESBL-producing isolate was found in 17/121 cases (14%), and that prior cephalosporin use (p = 0.039) and previous stay in the intensive care unit (p = 0.033) were signifi cant risk factors for infection with ESBLproducing K. pneumoniae. 24 Local and unit-specifi c surveillance data can inform antibiotic selection by providing guidance regarding the likely pathogens and their resistance profi les. This is particularly important for selection of empiric therapy and in community-acquired infections where microbiologic data and antibiotic use information may not be available.…”
Section: Resultsmentioning
confidence: 99%